Long-Term Follow-Up of the Fellow Eye in Patients Undergoing Surgery on One Eye for Treating Myopic Traction Maculopathy - Hui-Juan Xia; Wei-Jun Wang; Feng’E Chen; Ying Wu; Zhen-Yuan Cai; Wei Chen; Su-Qin Yu; Ying Fan (Journal of Ophthalmology)
Objective. To observe the fellow eye in patients undergoing surgery on one eye for treating myopic traction maculopathy. Methods. 99 fellow eyes of consecutive patients who underwent unilateral surgery to treat MTM were retrospectively evaluated. All patients underwent thorough ophthalmologic examinations, including age, gender, duration of follow-up, refraction, axial length, intraocular pressure, lens status, presence/absence of a staphyloma, and best-corrected visual acuity (BCVA). Fundus photographs and SD-OCT images were obtained. When feasible, MP-1 microperimetry was performed to evaluate macular sensitivity and fixation stability. Results. At an average follow-up time of 24.7 months, 7% fellow eyes exhibited partial or complete MTM resolution, 68% stabilized, and 25% exhibited progression of MTM. Of the 38 eyes with “normal” macular structure on initial examination, 11% exhibited disease progression. The difference in progression rates in Groups 2, 3, and 4 was statistically significant. Refraction, axial length, the frequency of a posterior staphyloma, chorioretinal atrophy, initial BCVA, final BCVA, and retinal sensitivity all differed significantly among Groups 1–4. Conclusions. Long axial length, chorioretinal atrophy, a posterior staphyloma, and anterior traction contribute to MTM development. Patients with high myopia and unilateral MTM require regular OCT monitoring of the fellow eye to assess progression to myopic pre-MTM. For cases exhibiting one or more potential risk factors, early surgical intervention may maximize the visual outcomes.